Peningkatan Kompetensi Technopreneurship Melalui Penerapan Business Model Canvas pada Siswa SMK Negeri 1 Mengwi - Jauzaa Maylia Suhendro; Ni Wayan Nanik Suaryani Taro Putri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
The era of digital transformation demands that the younger generation acquire technology-based entrepreneurship skills, or technopreneurship. However, in the context of Vocational High Schools (SMK), many students still lack understanding and skills in developing structured and applicable business models. This Community Service Program (PKM) was carried out to address this challenge, particularly at SMK Negeri 1 Mengwi, Badung, Bali, by leveraging local potential such as tourism and traditional culinary products. The training program focused on the use of the Business Model Canvas (BMC) as a visual tool for business planning, alongside the introduction of trending technologies such as digital marketing. The activities were implemented in four stages: pre-test, socialization, intensive training, business idea presentation, and post-test evaluation and reflection. A total of 36 students participated in this program. The results of the pre-test and post-test showed an increase in understanding of 53.85% in the aspect of technopreneurship and 58.33% in understanding the elements of the BMC. These findings indicate that practical and visual-based approaches are effective in fostering students’ strategic thinking, collaboration, and creativity in developing business ideas based on local potential and technology. This program also made a measurable and impactful contribution to strengthening vocational students' technopreneurship competencies